Pengambilan Keputusan Konsumen Terhadap Pemilihan Klinik Kecantikan - Supiah Ningsih (Jurnal Manajemen, Ekonomi, Keuangan dan Akuntansi, 2020)
This study aims to identify how self-concept in beauty clinic consumers. This research is descriptive in nature and uses a qualitative approach. Data collection techniques used were observation and interviews. The subjects consisted of 4 people characterized by women aged 20-28 years who visited the beauty clinic. Based on the interviews obtained, the results showed that subjects 1 and 3 did not feel they had the ideal self so the subjects felt dissatisfied with their condition and treated at the beauty clinic. Subjects 2 and 4 feel they have an ideal self by showing that physicality is not a standard in their lives, so visiting a beauty clinic is not a necessity for them but rather just looking after it. Keywords: self concept, beauty clinic, treatment